Polysaccharide from Pycnoporus sanguineus ameliorates dextran sulfate sodium‐induced colitis via helper T cells repertoire modulation and autophagy suppression. (13th April 2020) - Li, Muxia; Luo, Ting; Huang, Yong; Su, Jiyan; Li, Dan; Chen, Xiaohong; Zhang, Yifan; Huang, Longhua; Li, Shunxian; Jiao, Chunwei; Li, Wenzhi; Xie, Yizhen; et al.
Abstract : Inflammatory bowel disease (IBD) is a chronic autoimmune disease associated with various risk factors. Pycnoporus sanguineus (L.) Murrill is a saprotrophic fungus used worldwide for its industrial and medical purposes. Here, polysaccharide from P. sanguineus (PPS) was explored for its antiinflammatory potential in a murine colitis model of IBD induced by dextran sulfate sodium (DSS). PPS ameliorated the colitis as manifested by the lowered disease activity index (DAI), prolonged colon, and reduced serum lipopolysaccharide (LPS). PPS recovered the histological lesion by upregulating the expressions of Zonula occludens‐1 (ZO‐1), E‐cadherin, and proliferating cell nuclear antigen (PCNA). PPS inhibited the helper T cells (Th)‐mediated immune response by decreasing the proportions of Th cells (including Th2 cells, Th17 cells, and regulatory T cells), which was accompanied with reductions on myeloperoxidase (MPO) activity and releases of several interleukins and chemokines within the colon. Moreover, PPS exhibited an evident inhibition on autophagy, in which the ratio of light chain 3 (LC3) II/I was declined, while the expression of p62 and Beclin‐1 was increased. The present study highlighted important clinical implications for the treatment application of PPS against IBD, which relies on the regulation of Th cells repertoire and autophagy suppression to restore epithelium barrier.